2010
DOI: 10.1038/jid.2009.310
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Adherence Protein of Staphylococcus aureus Suppresses Disease by Inhibiting T-Cell Recruitment in a Mouse Model of Psoriasis

Abstract: Psoriasis is a T-cell-mediated inflammatory disease. Previous studies focused on lymphocyte function-associated antigen 1 (LFA-1)-expressing T cells as a molecular target for therapeutic intervention. By contrast, information on therapeutic effects and the underlying mechanism of blocking the LFA-1 counter receptor, ICAM-1 is scarce. Here, we used the CD18 (beta2-integrin) hypomorphic (CD18hypo) mouse model of psoriasis to investigate the therapeutic role of extracellular adherence protein (Eap) of Staphylococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 60 publications
0
15
0
1
Order By: Relevance
“…Epidermal deletion of JunB and c-Jun (26), the absence of endogenous MHC class II (27) in inbred mice, or reduced expression of the common chain of β2 integrin in CD18 hypomorphic PL/J mice (28) led to PsA-like disease symptoms. On the other hand, TLR7 ligation in innate immune cells by imiquimod, triggered Ps symptoms (29), while targeting of intracellular adhesion molecule-1 ameliorated the disease (30).…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal deletion of JunB and c-Jun (26), the absence of endogenous MHC class II (27) in inbred mice, or reduced expression of the common chain of β2 integrin in CD18 hypomorphic PL/J mice (28) led to PsA-like disease symptoms. On the other hand, TLR7 ligation in innate immune cells by imiquimod, triggered Ps symptoms (29), while targeting of intracellular adhesion molecule-1 ameliorated the disease (30).…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies showed that Eap and the C-terminal half of TSST1 (toxic shock syndrome toxin 1) as well as SEB (staphylococcal enterotoxin B) display homology, and Eap was thus shown to have superantigenic activity and to induce pro-inflammatory (IL6, TNFα) cytokine production by monocytes73. However, Eap has also been shown to exert numerous anti-inflammatory effects by inhibiting neutrophil adherence to the endothelium74, leukocyte recruitment in a murine bacterial peritonitis model75, T cell activation and recruitment to the dermis76.…”
Section: Protagonists Of the Plotmentioning
confidence: 99%
“…Eap and Emp non-covalently associate with the cell wall and promote staphylococcal adhesion to host proteins fibronectin, fibrinogen, vitronectin, and collagen [23]. Interestingly, Eap was found to decrease neutrophil and T-cell recruitment by binding to endothelial ICAM-1, preventing its interaction with leukocyte LFA-1 [2425]. The expression of Eap and Emp is not only dependent on Fur but also on the global regulators Agr, SarA and Sae underscoring the diverse signals that direct biofilm formation [26].…”
Section: Fur-mediated Expression Of Virulence Factorsmentioning
confidence: 99%